STRATEGIC OPPORTUNITIES TO INCREASE THE IMPACT OF SCIENCE AND TECHNOLOGY IN REGIONAL DEVELOPMENT: OPEN INNOVATION AND THE STRATEGIC VALUE OF HORIZONTAL SOCIAL NETWORKS - Russell, Linda (European Scientific Journal, ESJ, 2014)
This paper discusses the background to and theoretical grounding for the development of a collaborative project, initiated by the author with a local business-education foundation and two regional universities, to create a Web page based on the principles of open innovation to facilitate the transfer of science, technology and knowledge between disciplines and sectors to encourage innovation and development. It considers how open innovation can serve as a strategic device for overcoming organizational path dependence, vertical state and social hierarchies and embedded patron client relations, with the aim of achieving a greater role for science and technology in regional development in less favoured regions (LFR´s).